2020
DOI: 10.1002/ird.2493
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cyclic irrigation using moderately saline and non‐saline water on onion (Allium cepa L.) yield and soil salinization in semi‐arid areas of Northern Ethiopia*

Abstract: Due to the scarcity and/or unreliability of canal water supply, seepage water is haphazardly used for sole irrigation or in conjunction with canal water in most small-scale irrigation schemes in northern Ethiopia. This has been a major cause of low crop yield and has aggravated soil salinization. The problem is more exacerbated for onion, which is the major irrigated vegetable crop and is sensitive to salinity. Thus, it is essential to assess a sustainable way to use both water resources conjunctively for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…The attributes such as seed germination (%) and germination intensity decrease by increasing levels of salinity, as salinity and germination have antagonistic response (Baba et al, 2010 and. These results confirmed with findings of Yohannes et al (2020), who reported that increasing levels of salinity stops the plant growth hence decreasing the plant height.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The attributes such as seed germination (%) and germination intensity decrease by increasing levels of salinity, as salinity and germination have antagonistic response (Baba et al, 2010 and. These results confirmed with findings of Yohannes et al (2020), who reported that increasing levels of salinity stops the plant growth hence decreasing the plant height.…”
Section: Discussionsupporting
confidence: 92%
“…The increasing level of salinity reduces fresh and dry mass of leaves and plants. Furthermore, lesser number of leaves were also observed with increasing levels of salinity (Yohannes et al, 2020). This is might be due to the absorbance of less water due to plant tolerance mechanism activity.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations